Wellness from The Perspective of Malay Muslim Adults in Malaysia - Baharudin, Dini Farhana; Baharudin, Dini Farhana; Mahmud, Zuria; Amat, Salleh (‘Abqari Journal, 2015)
The purpose of this study was to explore Malay Muslim adults in Malaysia, their understanding on the concept of wellness. Using a qualitative design, data were collected through the use of semi- structured interviews with fourteen Malay Muslim adults between the ages of 21 to 60. Analysis of data from these interviews utilized the constant-comparative method. The findings showed that from the perspective of the participants as a whole, wellness is maintaining a good relationship with self, Allah and others. Aspects of wellness include physical, food and nutrition, psychological, financial, occupational, spiritual, social, environmental, and cultural domains. There was similarity in the view of the nature of wellness as multidimensional and encompassing the whole person. The findings highlight that the participants’ conceptualization of wellness relates to the Malay Muslims’ cultural background. This cultural uniqueness should be translated into a wellness-based counseling strategy for this specific ethnic group. This study also shows the importance of considering multicultural factors in understanding and dealing with a client. Recommendations and limitations are also discussed.